Data analytics and AI - Liebowitz, Jay (Boca Raton, FL : CRC Press, 2020)
"Two hot topics in recent years are data analytics and AI (artificial intelligence). These areas will continue to grow in importance for the foreseeable future. Unfortunately, both communities have not been communicating and collaborating with each other to build the necessary synergies. This book presents theory, applications, and case studies to bridge the gap between these fields"--
"An Auerbach Book."
OCLC-licensed vendor bibliographic record.
Keywords: Statistics -- Data processing; Artificial intelligence